EFFECT OF COVER CROPS AND BIOACTIVATORS IN COFFEE PRODUCTION AND CHEMICAL PROPERTIES OF SOIL - franco, Kleso silva; Carvalho Terra, Ana Beatriz; Teruel, Tiago Rezende; Mantovani, José Ricardo; Florentino, Ligiane Aparecida (Coffee Science - ISSN 1984-3909, 2018)
Coffee cultivation has great socio-economic relevance in Brazil for the employment and income generation and there is currently a constant search for sustainable management techniques. Among them, we can mention the use of cover crops and soil bioactivators. However, studies relating the use of these two techniques are still incipient. Based on this, the objective of this research was to evaluate the effect of the Penergetic® bioactivator associated with different cover crops on chemical properties of soil and coffee productivity. The experiment was carried out in a coffee field with Catuaí Vermelho cultivar IAC 144, in a randomized block design in a factorial scheme 4 (soil cover) x 2 (use or not of the Penergetic® bioactivator), consisting of control (without plant cover); oats (Avena strigosa) + forage turnip (Raphanus sativus L); oats (Avena strigosa) + forage turnip (Raphanus sativus L) + lupine (Lupine albus) + rye (Secale cereale) + vetch (Vicia sativa); Brachiaria brizantha (Urochloa brizantha), associated or not with the use of the Penergetic® bioactivator. The experiment was conducted for 6 months and after that period, the chemical properties of soil, the nutrient contents of the coffee plants, the development of the branches and the coffee productivity were analyzed. Data were analyzed by the Scott Knott test at 5% probability. It was verified the interaction between cover crops and the use of the Penergetic® bioactivator, positively influencing soil chemical characteristics, coffee nutrition and productivity.